2017
DOI: 10.1111/jzs.12168
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the systematics of Malagasy mongoose-like carnivorans (Carnivora, Eupleridae, Galidiinae) based on mitochondrial and nuclear DNA sequences

Abstract: The Malagasy carnivorans (Eupleridae) comprise seven genera and up to ten species, depending on the authority, and, within the past decades, two new taxa have been described. The family is divided into two subfamilies, the Galidiinae, mongoose‐like animals, and the Euplerinae, with diverse body forms. To verify the taxonomic status of Galidiinae species, including recently described taxa, as well as some recognized subspecies, we studied intrageneric genetic variation and structure, using both mitochondrial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The congeneric species is the Brown‐tailed vontsira Salanoia concolor , with a limited range in north‐east Madagascar. A genetic study, based mainly on samples from museum specimens, suggested that the isolated population of Lac Alaotra may not be a separate species (Veron, Dupré et al ., 2017). The same study also showed that the two species Broad‐striped vontsira Galidictis fasciata and Grandidier's vontsira Galidictis grandidieri form two separate clades but with a low level of genetic divergence and, therefore, should be considered subspecies of G. fasciata .…”
Section: New Species Of Small Carnivoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The congeneric species is the Brown‐tailed vontsira Salanoia concolor , with a limited range in north‐east Madagascar. A genetic study, based mainly on samples from museum specimens, suggested that the isolated population of Lac Alaotra may not be a separate species (Veron, Dupré et al ., 2017). The same study also showed that the two species Broad‐striped vontsira Galidictis fasciata and Grandidier's vontsira Galidictis grandidieri form two separate clades but with a low level of genetic divergence and, therefore, should be considered subspecies of G. fasciata .…”
Section: New Species Of Small Carnivoresmentioning
confidence: 99%
“…Based on recent studies, it appears that all seven genera of Malagasy carnivorans are monotypic (Veron, Dupré et al ., 2017; Veron & Goodman, 2018; Goodman & Veron, 2018).…”
Section: New Species Of Small Carnivoresmentioning
confidence: 99%
“…Family Eupleridae, the carnivore group endemic to the island of Madagascar, represents one of the least known and most threatened groups of carnivores in the world [9]. The taxonomic placement of this family of carnivores is still debated today, due to the isolation of this group over the last tens of millions of years [10].…”
Section: Introductionmentioning
confidence: 99%